Influência de invólucros de poliuretana e do número de lâminas no desempenho balístico de blindagens de Kevlar® XP S103 - Buffon Junior, Sérgio João (2018)
Ballistic protection vests can be used in individual protection against bullets impacts. Among the materials used as raw material, there are the polyamidebased fabrics, such as Kevlar® XP S103. The conjugated amour fabric layers number is decisive for designing to the different calibers and the projectiles velocities. Other main factors in the aramid based armors performance are the protection against aging agents like water and ultraviolet radiation, which in direct contact with the armor can lead to significant ballistic performance losses. This work aims to use of polyurethane derived from castor oil protection against aging agents such water and radiation, to measure Kevlar®/PU ballistic performance armors, comparing with a in use heat-sealed nylon and polyvinyl chloride solution and to evaluate the performance of different Kevlar® layers number targets, made only with fabric. The ballistic performance analyses were normalized by the National Institute of Justice Standard 0101.04, checking full perforation presence and plasticine indentation. The targets fracture analyze was performed by Scanning Electron Microscopy, and the chemical variation provoked by degradation agents were evaluated by Infrared spectroscopy. The better results were found in Kevlar® covered by PU samples, both to the unaged samples, as the degraded by the two agents. The polyurethane addiction was more effective than the nylon/PVC cases, even so, changes provoked by aging agents in chemical structure occurred in all samples. The targets with larger layers number presented better ballistic performance. There were identified armors designed for NIJ 0101.04, being the samples with the lowest aramid layers number not suitable to the standard III-A level. The theoretical model presented in the work pointed toward the real results, although errors were observed.